EVALUASI PENGARUH HORMON GONADOTROPIN PADA TINGKAT KEMATANGAN GONAD IKAN BOTIA (CHROMOBOTIA MACRACANTHUS) - Suci Hartati Liyana; Luthfiana Aprilianita Sari; Agustono Agustono (Universitas Muhammadiyah Gresik, 2019)
Botia fish (Chrombotia macracanthus), known as the clown loach, is a species of freshwater ornamental fish from the Cobitidae family whose distribution is limited to the islands of Borneo and Sumatra. The limitations of Botia fish distribution make it necessary to increase the maturity of the gonadal Botia fish to increase the breeding of these fish. The results of the evaluation of the effect of gonadotropin hormone on fish Botia carried out for four days and on the first female parent produced as many as 15,898 eggs with FR (Fertilization Rate) of 57.5% and HR (Hatching Rate) of 60.5%. The second Botia parent produces 10,872 eggs with FR (Fertilization Rate) of 96.5% and HR (Hatching Rate) of 13.7%. HCG serves to homogenize the size of the egg and accelerate gonadal maturity. Ovaprim serves to accelerate the ovulation process and stimulate spawning.